Hubungan Penyerapan Dana Desa Terhadap Indeks Desa Membangun di Kabupaten Kutai Barat Dengan Pendekatan Stochastic Frontier Analysis - Theodorus Sendjaja; Andhika Ahmad Putra; Nadiyah Kharisma Ataya (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Village funds, as the primary source of financing for village development, need to be evaluated for performance through the Village Development Index (IDM). The village funds usage serves as a useful indicator to assess the impact on development. However, the village funds usage faces inefficiency issues. This study aims to determine the relationship between the village funds usage and IDM, as well as to analyze the resulting level of efficiency. The frontier measurement method is used to achieve these research objectives. This study considers a time lag, as the impact of village fund absorption on IDM requires several time periods. The data analyzed includes the absorption of village funds by distribution sector in 2021 and the IDM value in 2023 for 190 villages in Kutai Barat Regency. The results of the study indicate that only the village funds usage in the field of disaster mitigation, emergency, and urgent village needs has a significant influence on IDM. Furthermore, there is a relationship between technical efficiency values and IDM scores.